Lycium barbarum Polysaccharides Improve Testicular Spermatogenic Function in Streptozotocin-Induced Diabetic Rats - Lei, Xiaocan; Huo, Peng; Wang, Yaohui; Xie, Yuanjie; Shi, Qingxiang; Tu, Haoyan; Yao, Jun; Mo, Zhongcheng; Zhang, Shun (Frontiers in Endocrinology, 2020)
The objective of this study was to investigate the protective effects of Lycium barbarum polysaccharides (LBP) on testicular spermatogenic function in streptozotocin (STZ)-induced diabetic rats. Compared to the control group, blood glucose levels were significantly increased and the insulin resistance was markedly aggravated in STZ-induced diabetic rats. Further, the weight of testis and epididymis, and the sperm number and motility in diabetic rats were decreased. Pathological changes were also observed in the spermatogenic tubules along with decreased number of spermatogenic cells, downregulated proliferating cell nuclear antigen (PCNA) expression, and increased cell apoptosis in the testes. Compared to the saline-treated diabetic rat group, metformin and LBP treatment significantly decreased the level of blood glucose and improved insulin resistance and testicular function. After treatment with metformin and LBP, the pathological changes in the spermatogenic tubules improved significantly with an increase in the number of spermatogenic cells, upregulation of PCNA, and suppression of apoptosis in the testes. The expression of sirtuin 1 (SIRT1) and hypoxia-inducible factor 1-alpha (HIF-1α) in diabetic testes were also upregulated by metformin or LBP treatment. In summary, LBP exerted protective effects by increasing cell proliferation, inhibiting cell apoptosis and regulating SIRT1/HIF-1α expression in the testes of diabetic rats.